Peningkatan Hasil Belajar melalui Model Problem Based Learning Materi Trigonometri Kelas X Tata Busana - Nur Hamidah (UNION : Jurnal Ilmiah Pendidikan Matematika, 2021)
This research is a Classroom Action Research. The research subjects were students of class X Fashion Design 2 SMK Negeri 2 Temanggung in 2019/2020, totaling 36 students consisting of 36 female students and 0 male students. The instruments used in this study were test instruments and non-test instruments. The non-test instruments consist of observation sheets, field notes and documentation. The data collection technique was done by using test techniques and non-test techniques. Analysis and data processing using quantitative techniques and qualitative techniques. The research was carried out in two cycles with each cycle consisting of four stages, namely planning, action, observation and reflection. The average individual test score increased from 61.53 in cycle 1 to 88.15 in cycle 2. Completeness of classical learning also increased by 66.7% from 33.3% to 100%. The research results have been able to answer the problem formulation, achieve research objectives and prove the research hypothesis, namely the use of Problem Based Learning can improve learning outcomes on Trigonometry material.